Perceptions of the elderly about cardiovascular risk factors - Cleusa Maria Richter; Luiz Antonio Bettinelli; Adriano Pasqualotti; Paulo Ricardo Nazário Viecili; Alacoque Lorenzini Erdmann; Giovana Dorneles Callegaro Higashi (Rev Rene)
A qualitative exploratory study that aimed to understand the perceptions of a group of elderly people on cardiovascularrisk factors. The study included 100 elderly of both sexes, of the city of Cruz Alta-RS, Brazil, 2009. Data collectionhappened through semi-structured interviews. From the thematic analysis were constructed the following threecategories: Lack of knowledge on the diseases (diabetes mellitus and hypertension) as cardiovascular risk factors; Safetyin drug therapy to minimize the risk factors; and Eating habits and healthy lifestyles. Based on the results, we suggestprioritizing the development of an educational process in multidisciplinary health directed to the specifics of the elderly,in order to reduce the cardiovascular risk factors and qualify their living.